ChemInform Abstract: Palladium on Carbon‐Catalyzed Aqueous Transformation of Primary Alcohols to Carboxylic Acids Based on Dehydrogenation under Mildly Reduced Pressure. Issue 33 (August 2015) - Sawama, Yoshinari; Morita, Kosuke; Asai, Shota; Kozawa, Masami; Tadokoro, Shinsuke; Nakajima, Junichi; Monguchi, Yasunari; Sajiki, Hironao
Abstract The clean and first dehydrogenation of primary alcohols to carboxylic acids in presence of a heterogeneous catalyst is presented.